GEOLOGY OF MERU-CHEPOR AREA WITH EMPHASIS ON GRANITE RESOURCE - Ong , Kar Ying (Universiti Teknologi PETRONAS, 2014)
The study is conducted to investigate the general geology of the Meru-Chepor area and to determine the suitability of the granite for use as construction aggregates. There is not much research papers being published on this area and most of the geological features are not well understood. Hence, a geological map of scale of 1:40000 is produced. Results showed that the study area is underlain by coarse-grained porphyritic granite which is part of the Kledang Range to west, intruding out of the granite is a 100m-200m wide, 8km long quartz dyke to the east. The area is underlain by alluvium or tailing sand with limestone (possibly) as bedrock. Perak has a number of quartz quarries producing silica and in Chepor, there is one moderately large quartz quarry. From site observation and all of the result obtained, abundant granites resource is also available in Perak particularly in Meru-Chepor area. In order to determine the suitability of the granite for construction use, commercial test result is conducted to make general assessment of suitability of this rock type to be aggregate source rock. Rock aggregate test is conducted for granite samples collected at Persiaran Chepor Indah. The result obtained is compared to the Malaysian standard for rock aggregate used in the construction industry provided by Department of Public Work (Jabatan Kerja Raya, J.K.R). This is done by assessing the quantitative compliance requirement for particle shape, shell grading, cleanliness and mechanical property of rock aggregates. The result shows that the Water Absorption Value, Flakiness Index, Aggregate Impact value, Aggregate Crushing Value and Los Angeles Abrasion test values are all well within the acceptable J.K.R. Limit. Thus, it is concluded that these granite aggregates is suitable to be used for road pavement, concrete and even airfield pavement. Investigation showed that there is at least one other site along the Kledang Range which can be developed as a new quarry. A potential quarry site can be located at the northern end of Kledang Range due to its strategic location. It is located at least 3km away from local resident and at the backside of Kledang Range which provide a shield for the resident from quarry dust and sound pollution. The potential quarry has steep slope which provides sufficient amount of granite.